2016
DOI: 10.1038/srep29059
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the “carrier” state for foot-and-mouth disease from the dynamics of virus persistence in endemically affected cattle populations

Abstract: The foot-and-mouth disease virus (FMDV) “carrier” state was defined by van Bekkum in 1959. It was based on the recovery of infectious virus 28 days or more post infection and has been a useful construct for experimental studies. Using historic data from 1,107 cattle, collected as part of a population based study of endemic FMD in 2000, we developed a mixed effects logistic regression model to predict the probability of recovering viable FMDV by probang and culture, conditional on the animal’s age and time sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
4
23
1
Order By: Relevance
“…Similar to results of our current study, differences in extinction rates amongst subclinical T A B L E 6 Generalized estimating equation analysis of per cent of positivity results in subclinical and clinically infected animals exposed to foot-and-mouth disease virus and clinically infected animals were not significant (Hayer et al, 2017). However, findings in our study contradict the probabilistic analysis by Barend et al (2016), which suggested that the virus recovery would be expected to be close to zero by 9 months after an outbreak (Barend et al, 2016) There are only a few reports that have studied the duration of the presence of anti-NSP antibodies after natural FMDV infection in animals (Elnekave, Shilo, Gelman, & Klement, 2015;Hayer et al, 2017). In our study, more than 75% of animals were seropositive at all time points within 1 year of the outbreak.…”
Section: Examination Of Temporal Changes In Pp Values In Clinicallycontrasting
confidence: 83%
See 1 more Smart Citation
“…Similar to results of our current study, differences in extinction rates amongst subclinical T A B L E 6 Generalized estimating equation analysis of per cent of positivity results in subclinical and clinically infected animals exposed to foot-and-mouth disease virus and clinically infected animals were not significant (Hayer et al, 2017). However, findings in our study contradict the probabilistic analysis by Barend et al (2016), which suggested that the virus recovery would be expected to be close to zero by 9 months after an outbreak (Barend et al, 2016) There are only a few reports that have studied the duration of the presence of anti-NSP antibodies after natural FMDV infection in animals (Elnekave, Shilo, Gelman, & Klement, 2015;Hayer et al, 2017). In our study, more than 75% of animals were seropositive at all time points within 1 year of the outbreak.…”
Section: Examination Of Temporal Changes In Pp Values In Clinicallycontrasting
confidence: 83%
“…Although transmission from persistently infected cattle has not been proven under experimental conditions (Ilott, Salt, Gaskell, & Kitching, 1997;Parthiban, Mahapatra, Gubbins, & Parida, 2015), the presence of FMDV carriers in a population can severely impact foreign trade of all animal products (Kitching et al, 2007). In addition, the dynamics of the FMDV carrier state is relatively understudied in field conditions (Barend et al, 2016;Hayer et al, 2017).…”
mentioning
confidence: 99%
“…No serotype A viruses were recovered from OPC cattle OPF samples collected in 2016 despite the fact that these animals were alive during the previous outbreak. Such findings are not surprising given the fact that the carrier stage, during which cattle may show persistent infection in the nasopharynx, usually lasts only one year (Hayer et al, 2018, Bronsvoort et al, 2016 and up to 28 months under some conditions . The only serotype to be recovered from OPC cattle OPF samples was serotype O, which was closely related to an outbreak of serotype O in Subukia, Nakuru, and another location from which OPC occasionally purchases animals.…”
Section: D) Discussionmentioning
confidence: 96%
“…In humans, the probability of persistent Hepatitis B infection decreased with age (Ott et al 2012), whereas, in some populations, the probability of persistent HPV infection increased with age (Castle et al 2005). In cattle, the probability of persistent foot-andmouth disease virus infection decreased with age (Bronsvoort et al 2016), however in wild rodents, no association was observed between the duration of cowpox infection and age (Hazel et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…In cattle, the probability of persistent foot‐and‐mouth disease virus infection decreased with age (Bronsvoort et al . ), however in wild rodents, no association was observed between the duration of cowpox infection and age (Hazel et al . ).…”
Section: Discussionmentioning
confidence: 99%